2023
DOI: 10.1371/journal.pone.0279653
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation measures after cardiac arrest (CMACA)

Abstract: Background During cardiac arrest (CA) and after cardiopulmonary resuscitation, activation of blood coagulation and inadequate endogenous fibrinolysis occur. The aim of this study was to describe the time course of coagulation abnormalities after out-of-hospital CA (OHCA) and to examine the association with clinical outcomes in patients undergoing targeted temperature management (TTM) after OHCA. Methods This prospective, multicenter, observational cohort study was performed in eight emergency departments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the relationship between coagulation changes after CA and prognosis, as well as attempts to use various indicators and models to predict the clinical outcomes, 19 22 but there is still a lack of indicators and models that are accepted by most clinicians. Regardless of the coagulation indices used to assess the prognosis of CA patients, however, we cannot avoid the relevant studies of sepsis because sepsis and PCAS have very similar pathophysiological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the relationship between coagulation changes after CA and prognosis, as well as attempts to use various indicators and models to predict the clinical outcomes, 19 22 but there is still a lack of indicators and models that are accepted by most clinicians. Regardless of the coagulation indices used to assess the prognosis of CA patients, however, we cannot avoid the relevant studies of sepsis because sepsis and PCAS have very similar pathophysiological characteristics.…”
Section: Discussionmentioning
confidence: 99%